Potential role of M2 TAMs around lymphatic vessels during lymphatic invasion in papillary thyroid carcinoma - Takanobu Kabasawa (Nature Portfolio, 2021)
Abstract The aim of this study was to examine whether lymphatic invasion in papillary thyroid carcinoma (PTC) occurs when tumour-associated macrophages (TAMs) injure lymphatic vessels together with cancer cells. While there was no difference in the lymphatic vessel density in PTC and follicular thyroid carcinoma (FTC), the number of TAMs around the lymphatic vessels was increased in PTC compared to that in FTC. In particular, TAMs were observed together with cancer cells in lymphatic invasive lesions, and the number of M2 cells inside and outside the lymphatic vessels showed a significant correlation. MMP-2 mRNA was expressed in nonneoplastic stromal cells as well as cancer cells, and double immunofluorescence staining confirmed M2 positivity. Consequently, this study reveals that M2 TAMs around lymphatic vessels within the tumour border of PTC may be associated with the lymphatic invasion of cancer cells. This study represents a step forward in elucidating the mechanism of lymphatic invasion.